REQUIRED URBANISM: CRAIG MORRIS AND INCA URBAN PHENOMENON - Tantaleán, Henry (2010)
In this article we discuss one of the more significant contributions of Craig Morris for the explanation of the Inca Urbanism. Although Craig Morris didn’t escape to the use of general theoretical models and basic concepts derived from historic-cultural and procesualist perspectives, popular in his epoch, given his context of academic formation, thanks to the continual test of his approaches against the archaeological reality, the development of ad hoc methodology and a wide standpoint about the pre-capitalists social phenomena he could overcome such models and, later, offer us archaeological explanations more coherent with the Inca social reality.